2022
DOI: 10.1002/adfm.202112754
|View full text |Cite
|
Sign up to set email alerts
|

High Spin Hall Conductivity Induced by Ferromagnet and Interface

Abstract: Spin-orbit-torque (SOT) offers a highly attractive perspective for manipulating magnetization dynamics in magnetic nanostructures. SOT is been observed and studied in various systems. However, limited by the efficiency, SOT-induced switching of the ultrahard ferromagnet is still extremely difficult and a further improvement in efficiency is requested. Here, the SOT is reported in chemically disordered soft Fe 0.5 Pt 0.5 and Pt/Fe 0.5 Pt 0.5 bilayers. Due to the magnetization-strengthened spin Hall effect, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…As another material option, Li et al studied the SOT‐driven magnetization switching in FePt ferromagnet and observed the magnetization switching at J = ≈7.3 × 10 11 A m −2 (and H x = 1500 Oe). [ 181 ] A higher charge‐to‐spin current conversion efficiency of 1.11 was observed in this study (corresponding resistivity of ≈100–150 45 μΩ cm). Meanwhile, Tao et al also reported the field‐free magnetization switching in the L 1 0 ‐FePt system at a similar current density of ≈3 × 10 11 A m −2 .…”
Section: Spin–orbit Torquementioning
confidence: 51%
“…As another material option, Li et al studied the SOT‐driven magnetization switching in FePt ferromagnet and observed the magnetization switching at J = ≈7.3 × 10 11 A m −2 (and H x = 1500 Oe). [ 181 ] A higher charge‐to‐spin current conversion efficiency of 1.11 was observed in this study (corresponding resistivity of ≈100–150 45 μΩ cm). Meanwhile, Tao et al also reported the field‐free magnetization switching in the L 1 0 ‐FePt system at a similar current density of ≈3 × 10 11 A m −2 .…”
Section: Spin–orbit Torquementioning
confidence: 51%
“…After several pulses, no degeneration in R H is observed, so the influence of Joule heat in switching can be negligible. 57 As the amplitude of the current pulse changes, R H shows steady multiple values, which proves that the characteristics of synapses can be simulated by setting different current sequences. 5,58 These results indicate the great potential for applications of similar structures in high-density magnetic storage or memristors for neuromorphic computing.…”
Section: Spin Torque Measurementsmentioning
confidence: 85%
“…Meanwhile, arising from the interplay between SHE and novel physics, many fascinating phenomena are observed, and recent years have witnessed the rapid development of this field. For example, combined with the established physics of the dissipationless quantum Hall effect, the intrinsic SHE leads to the prediction and subsequent experimental verification of the quantum spin Hall effect (QSHE) in 2D systems, initiating the research field of topological insulators.…”
mentioning
confidence: 99%